KEMANDIRIAN GERAKAN CINTA SONIK (SAMPAH ORGANIK) MENGELOLA SAMPAH DARI SUMBER RUMAH TANGGA DESA LENGKONG KECAMATAN BOJONGSOANG KABUPATEN BANDUNG - Kurniawati, Ratna Dian; Fauziah, Diah Adni; Stellata, Alyxia Gita; Munawaroh, Madinatul; Oktafiani2, Hani; Setiawati, Rita; Nurhaliza, Farah; Hidayana, Haiqal Akbar; Nugraha, Mochamad Faisal (Jurnal Pepadu, 2024)
Efforts to process waste at the source are a must considering that the Sarimukti Landfill (TPA) only accepts 50% of waste. These efforts include reducing waste with Reduce, Reuse and Recylce method and processing waste independently through simple composting. RT 01/013 area of Lengkong Village, Bojongsoang District is a densely populated settlement that has had a Reduce, Reuse, Recycle Waste Management Site (TPS 3R) for the Bagja Self-Help Group (KSM) since 2021. This TPS 3R can only accommodate the waste of 3 RW out of 17 RW in Lengkong Village. This means that the existence of TPS 3R KSM Bagja hasn’t been able to accommodate the volume of waste. This community service aims to increase community knowledge, especially RT 01/013 Lengkong Village about processing household organic waste. The community service method with the theme "Gerakan Cinta Sampah OrgaNIK" (Cinta SONIK) includes counseling, education, organic waste processing practices and providing waste processing equipment assistance in the form of biopori making tools and EM4 as a decomposer of organic matter. After the organic waste processing education, there was an increase in the average knowledge of participants during the posttest to 84.73, higher than the pretest value of 62.63. Data analysis states that there’s a significant difference between the knowledge of respondents before and after being given education about processing household organic waste. The community service that has been carried out has succeeded in increasing the knowledge of the RT 01/013 community in Lengkong Village.